(untitled) (Research, Society and Development, 2020)
The quality of vegetable products is directly linked to the techniques used in the field, in order to ensure safe and healthy products to health. In this context, the use of yeasts with potential for biological control proved to be a promising alternative to assure the safety of these foods. Fermentation processes have been used to promote the development of many products, including the production of yeast biomass. The objective of this work was to verify the influence of the aeration rate and the fed batch process in the production of yeast biomass. A yeast strain with biological control potential, belonging to Embrapa’s Semi-Arid crop collection, was subjected to simple batch cultivation and fed with different aeration rates (3, 4, 6 and 8 L.ar/min) and concentration of carbon source in the feed medium (200, 400 and 600 g/L). The highest biomass (6.99 g/L) after 24 hours of fermentation was observed in the experiment that used an aeration rate of 8 L.ar/min. Regarding the concentration of the carbon source in the feed medium, it was found that the concentration of 200 g/L favored a greater total biomass (11.21 g/L) and reduced the production of ethanol (0.65 g/L ), while the concentration of 600 g/L favored less biomass production (7.90 g/L) and higher ethanol production (9.26 g/L). Thus, it was found that the aeration rate and the fed batch process favor the fermentation strategy, as they contribute to the production of yeast biomass and the overall yield of the process.